Extensive ossification of the paraspinal ligaments in a patient with vitamin D-resistant rickets: Case report with literature review. (2016) - Hirao, Yujiro; Chikuda, Hirotaka; Oshima, Yasushi; Matsubayashi, Yoshitaka; Tanaka, Sakae
Highlights: This is the case of a 64-year-old woman with VDRR and extensive spinal ossification. This case was followed up for over 30 years. Imaging studies demonstrated fusion of the entire spine below the C2 vertebra. Mobility at the craniovertebral junction caused C1-level spinal cord compression. The pathology mimicked ankylosing spondylitis. Abstract: Introduction: Ectopic ossification of the spinal ligaments is not uncommon in patients with Vitamin D-resistant rickets (VDRR), but the long-term consequences of this condition have not been reported. Presentation of case: The case was a 65-year-old female with VDRR who reported progressive weakness of the upper extremities, difficulty walking, neck pain, and numbness in the left arm. Imaging studies demonstrated cord compression with ectopic ossification at the rim of the occipital bone and OPLL at C1 level. Ankylosis of the whole spine below the C2 vertebra was also noted with preserved mobility only at the craniovertebral junction. Discussion: Our report showed that ectopic ossification of the spinal ligament can result in ankylosis of the entire spine in patients with VDRR. In such patients, the segments with remaining mobility are considered to be at high risk of developing myelopathy due to increased stress at the junction. Conclusion: The present case underscores the importance of providing long-term follow-up in VDRR patients presenting with ectopic ossification of the spinal ligaments. In particular, physicians should pay close attention to the possibility of myelopathy in any segments with preserved mobility.